A Case of Post-Endobronchial Ultrasound Polymicrobial Pericarditis and Mediastinitis in Metastatic Renal Cell Carcinoma - Viktor Sekowski; Waël Hanna (Case Reports in Oncology)
Introduction: Endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) is a frequently used bronchoscopic method for sampling centrally located tumors and accessible mediastinal lymph nodes. It is widely employed for staging and obtaining tissue diagnosis in lung cancer, but it can also be used for other conditions with mediastinal lymph node metastases. Although the reported complication rate for EBUS-TBNA varies, it consistently remains low, including for severe infectious complications such as pericarditis and mediastinitis. Case Presentation: We present a unique case of polymicrobial pyogenic pericarditis, mediastinitis, and death in a patient who underwent EBUS-TBNA for the evaluation of solitary mediastinal lymphadenopathy in the background of previously resected renal cell carcinoma. There were no complications during her procedure and her mediastinal lymph node biopsy confirmed metastatic renal cell carcinoma. However, 23 days after her procedure, she presented to the emergency department with sepsis and cardiac tamponade. Pericardial fluid cultures and computed tomography imaging confirmed polymicrobial pyogenic pericarditis and mediastinitis. Conclusion: While complications from EBUS-TBNA are rare, clinicians need to be aware that pericarditis and mediastinitis are possible life-threatening complications in order to facilitate early recognition and interventions.